Development and Preliminary Validation of the “Teacher of Physical Education Burnout Inventory” (TPEBI) in Arabic Language: Insights for Sports and Occupational Psychology - Chalghaf, Nasr; Guelmami, Noomen; Slimani, Maamer; Del Puente, Giovanni; Re, Tania Simona; Zerbetto, Riccardo; Maldonado Briegas, Juan José; Guglielmi, Ottavia; Garbarino, Sergio; Azaiez, Fairouz; Bragazzi, Nicola Luigi (Frontiers in Psychology, 2019)
Background: Burnout is an inappropriate response to chronic work stress, leading to Emotional exhaustion (EE), Depersonalization (D) and low Personal accomplishment (PA). Burnout can affect workers in the helping professions. To quantitatively assess the burnout level among teachers, Maslach has adapted the “Maslach Burnout Inventory” (MBI) to the educational environment (the so-called MBI Educators Survey version or MBI-ES). Among teachers, sports and physical education teachers may suffer from burnout due to high workload. Aims: No reliable psychometric tool in Arabic language exists that can be used to measure the burnout level among sports and physical education teachers. The objective of the present study was to develop a burnout measurement scale according to the Maslach's 3-dimensional theoretical model for physical education teachers in Tunisia and to test its factor structure, in terms of internal consistency/reliability, predictive validity, and sensitivity. Methods: A total of 525 Tunisian teachers teaching in secondary schools from different Tunisian governorates volunteered to participate in this study. The sample comprised of 285 males (54.3%) and of 240 females (45.7%). More in detail, 327 were teachers of primary school of physical education (62.3%) and 198 teachers of secondary school (37.7%). Teachers were administered both the ad hoc developed “Teacher of Physical Education Burnout Inventory” (TPEBI) and the MBI-ES. Both exploratory (EFA) and confirmatory (CFA) factor analyses were performed. Results: The Cronbach’s alpha coefficients were excellent (0.93, 0.94, and 0.91 for EE, D and PA, respectively). The correlation matrix indicated significant correlations between the TPEBI and MBI-ED dimensions. However, CFA fit indices were not completely satisfactory. Conclusions: Given the good EFA factor loadings, the correlation matrix, the sensitivity analysis and the excellent internal consistency, it can be concluded that the TPEBI is a reliable psychometric tool that can be used to quantitatively assess the burnout level among teachers of physical education in the Arabic-speaking world. However, considering the CFA fit indices, further modifications to fully support the model are warranted.